2011
DOI: 10.1016/j.pbb.2011.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Decreased response to social defeat stress in μ-opioid-receptor knockout mice

Abstract: Substantial evidence exists that opioid systems are involved in stress response and that changes in opioid systems in response to stressors affect both reward and analgesia. Reportedly, mice suffering chronic social defeat stress subsequently show aversion to social contact with unfamiliar mice. To further examine the role of opioid systems in stress response, the behavioral and neurochemical effects of chronic social defeat stress (psychosocial stress) were evaluated in μ-opioid-receptor knockout (MOR-KO) mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 46 publications
3
29
1
Order By: Relevance
“…Also, our findings agree with those of Alfonso and colleagues, who had shown that when mice were subjected to repeated restraint stress, hippocampal BDNF messengers were down-regulated as measured by RT-PCR (Alfonso et al, 2006). More importantly, chronic social defeat stress has also been shown to decrease expression of hippocampal BDNF (Komatsu et al, 2011). Finally, it should be notified that the work performed in Nestler lab indicated that detailed mRNA analysis of whole mouse hippocampus revealed that chronic defeat stress induced an approximately threefold reduction in BDNF mRNA levels (Tsankova et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…Also, our findings agree with those of Alfonso and colleagues, who had shown that when mice were subjected to repeated restraint stress, hippocampal BDNF messengers were down-regulated as measured by RT-PCR (Alfonso et al, 2006). More importantly, chronic social defeat stress has also been shown to decrease expression of hippocampal BDNF (Komatsu et al, 2011). Finally, it should be notified that the work performed in Nestler lab indicated that detailed mRNA analysis of whole mouse hippocampus revealed that chronic defeat stress induced an approximately threefold reduction in BDNF mRNA levels (Tsankova et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…It has been suggested that MOR function is involved in the regulation of anxiety and arousal (Thorsell, 2013) and may contribute to the development of several stress-related psychiatric disorders such as depression and anxiety (Komatsu et al, 2011). In the PET study by Love and colleagues (2009), subjects with high deliberation displayed a lower baseline MOR binding potential, and their endogenous opioid system response to stress was lower than among low deliberation group, whereas high impulsiveness was associated with higher MOR binding potential in several brain areas essential for motivation and reward.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicates that the µ-opioid receptor (MOR) serves a key role in the regulation of mood and emotional disorders (5)(6)(7). In particular, it has been observed that withdrawal of endogenous opioid peptides is associated with the development of PMS, and decreased levels of opioid peptides are considered as a marker of the condition (8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%